Sediment and contaminant transport in surface waters - Lick, Wilbert J. (CRC Press, 2009)
This volume emphasizes the erosion, deposition, flocculation, and transport of fine-grained, cohesive sediments; the effects of finite rates of sorption on the transport and fate of hydrophobic contaminants; and the effects of major events such as floods and storms. Despite these emphases, the overall goal of the text is to present a general description and understanding of the transport of sediments and contaminants in surface waters as well as procedures to quantitatively predict this transport.